2005
DOI: 10.1194/jlr.m500249-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein [a] is cleared from the plasma primarily by the liver in a process mediated by apolipoprotein [a]

Abstract: [a] have been described in humans, ranging in size from Ͻ 300 kDa to Ͼ 800 kDa (2).Plasma levels of Lp[a] vary greatly between individuals, from Ͻ 1 mg/dl to Ͼ 100 mg/dl (2). The source of most of this variability in plasma concentrations is variability in the production rate of Lp[a] (3, 4), which, in turn, is controlled largely by the apo[a] gene locus (5). Apo[a] is synthesized by hepatocytes and rapidly associates with LDL after secretion to form Lp[a] in the sinusoids of the liver (2, 6). Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 58 publications
4
59
0
3
Order By: Relevance
“…This is consistent with in vivo data demonstrating that apo(a) competitively inhibits the plasma clearance of Lp(a) in mice ( 35 ). Although it has been more than 50 years since the discovery of Lp(a) ( 36 ), the receptor(s) involved in Lp(a) uptake are still not well defi ned.…”
Section: Hdl-c Abca1-mediated Cholesterol Effl Ux and Lipoprotein(asupporting
confidence: 78%
See 2 more Smart Citations
“…This is consistent with in vivo data demonstrating that apo(a) competitively inhibits the plasma clearance of Lp(a) in mice ( 35 ). Although it has been more than 50 years since the discovery of Lp(a) ( 36 ), the receptor(s) involved in Lp(a) uptake are still not well defi ned.…”
Section: Hdl-c Abca1-mediated Cholesterol Effl Ux and Lipoprotein(asupporting
confidence: 78%
“…The LDL-R has been implicated in Lp(a) clearance in HepG2 cells ( 37 ) and LDL-R overexpressing mice ( 38 ), possibly through a bystander effect where apoB-100 of Lp(a) is recognized by LDL-R leading to internalization of Lp(a). However, Lp(a) clearance is unaffected by LDL-R defi ciency in humans ( 39 ) or mice ( 35 ), suggesting that the overall magnitude of this pathway appears to be modest in vivo, and it is likely that the apo(a) moiety is mostly responsible for receptor-mediated catabolism of Lp(a), as suggested by this study.…”
Section: Hdl-c Abca1-mediated Cholesterol Effl Ux and Lipoprotein(amentioning
confidence: 70%
See 1 more Smart Citation
“…ApoE and the receptors that mediate the binding and uptake of apoB100 containing lipoproteins have been proposed as having a role in Lp(a) catabolism. However, the nature of the major receptor(s) that mediate the plasma clearance and tissue uptake of Lp(a) remains to be determined [182]. Clearance of Lp(a) is not well understood, but the LDL receptor or apo(a) size does not appear to be the main determinant of clearance [183].…”
Section: Lipoprotein(a)mentioning
confidence: 99%
“…The mechanism may include an increased turnover-time of plasma Lp(a) ( 29 ), and the uremia-induced increase of plasma Lp(a) may be isoform-dependent (30)(31)(32). It has been suggested that the increase of Lp(a) in uremic individuals refl ects decreased clearance in the kidney ( 28,33,34 ), although kinetic studies in rabbits and mice using radiolabeled Lp(a) indicate that the liver is the major organ for clearance of plasma Lp(a) in nonuremic animals ( 35,36 ). Elevated Lp(a) has been associated with increased risk of cardiovascular disease in relatively small studies of uremic patients ( 37,38 ).…”
Section: Apo(a) Lp(a) Apob and Oxpl Measurementsmentioning
confidence: 99%